PERANAN PROYEKSI STITCH VIEW LONG LEG PADA PEMERIKSAAN KNEE JOINT DENGAN INDIKASI OSTEOARTHRITIS - Purwa Puspita Arum; Panji Wibowo Nurcahyo (JRI (Jurnal Radiografer Indonesia), 2021)
ABSTRACT Introduction: Long Leg View is an x-ray examination of all parts of the lower extremity using a long vertical cassette which aims to measure the angle between the mechanical axis of the femur and tibia. Knee Joint examination with indications of osteoarthritis at the Radiology Installation of RSUP Dr. Sardjito Yogyakarta uses supine AP projection, Lateral recumbent, Skyline, and Stitch View Long Leg. Methods: This research is a qualitative research with a case study approach. Collecting data by means of observation, documentation, and in-depth interviews with patients, sending doctors, radiologists, and radiographers. Data collection was carried out in March 2018 at the Radiology Installation of Dr. RSUP. Sardjito Yogyakarta. The data obtained were analyzed using an interactive model. Results: On the Stitch View Long Leg examination at the Radiology Installation, Dr. Sardjito Yogyakarta uses a collimation area from the pelvis to the ankle joint. According to the resident doctor of orthopedic surgery and traumatology, Dr. Sardjito Yogyakarta, Stitch View Long Leg is able to see the shape of the foot formation, namely the O formation or X formation. In addition, according to radiology specialists, looking at the alignment deviation of the lower extremities can be used to assess the grade of osteoarthritis. Under normal conditions, the anatomical axis of the femur and tibia forms an angle of 6º ± 2º, while the mechanical axis line under normal conditions is 8 mm ± 7 mm medial to the center of the knee joint line. The alignment of varus and valgus has been associated with the development of medial or lateral osteoarthritis. Conclusion: Stitch View Long Leg aims to assess the grade of osteoarthritis through assessment of lower extremity alignment deviations, see the overall mechanical and anatomical alignment of the lower extremities, help determine the calculation of the angle of bone cutting during Total Knee Replacement surgery, and see the right and left symmetrical balance of genu.